Identifikasi Bakteri Coli fecal dan Coli non fecal pada Minuman Es Teh Jumbo yang Dijual di Jalan Karya, Kecamatan Medan Barat - Sri Muri Dasa Wardhani; Latifah Ningrum Abdillah; Muhammad Rifqi (Journal of Microbiology, Biotechnology and Conservation, 2026)
Iced tea is a popular beverage among the public, but the processing and serving of this drink carry a risk of bacterial contamination. This study aimed to identify the presence of fecal and non-fecal coliform bacteria in jumbo-sized iced tea sold on Jalan Karya, Medan Barat District. The study employed a quantitative descriptive method using the Most Probable Number (MPN) technique on eight samples. Testing was conducted in a preliminary stage using Lactose Broth (LB) and a confirmation stage using Brilliant Green Lactose Bile Broth (BGLB), with incubation at 44.5°C for fecal coliforms and 37°C for non-fecal coliforms. The results showed that all samples tested positive for both fecal and non-fecal coliform bacteria. The MPN values for fecal coliforms ranged from 10 to ≤979 MPN/100 mL, while those for non-fecal coliforms ranged from 265 to ≤979 MPN/100 mL. All results exceeded the maximum limits set forth in Regulation of the Minister of Health of the Republic of Indonesia No. 492/MENKES/PER/IV/2010. Thus, none of the jumbo iced tea samples met the microbiological quality requirements.